Analisis Penerapan Belajar Mandiri Pada Materi Al-Qur’an Hadis Kelas VIII di MTSN Agam - Mansyah, Iqbal Doni; Monia, Fenny Ayu; J, Jasmienti; Ariza, Hidra (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to describe the application of independent learning on AL-Qur'an hadith material at MTsN 7 Agam and describe the steps for implementing independent learning on AL-Qur'an hadith material at MTsN 7 Agam. The research method used is a qualitative descriptive method with data collected through observation, interviews and documentation. The results of the research show that the application of independent learning methods at MTsN 7 Agam is by memorizing verses or hadiths related to the material, by being given assignments to understand the material, and by studying in groups in the classroom. There are several steps in implementing independent learning at MTsN 7 religions including: 1). Set a regular schedule. 2). ⁠Using reading sources such as books and the Koran.3). Determine a comfortable learning environment. 4). Consistent in learning.5). Monitor and evaluate Progress.6). Seek guidance if you have difficulty. Apart from the steps and implementation, there are also obstacles in implementing this independent learning method, the obstacles that hinder the implementation of independent learning at MTsN 7 Agam are: lack of motivation within students and interference from their environment.